Discovery of novel sulphonamide hybrids that inhibit LSD1 against bladder cancer cells - Jia Liu; Xingwang Zhu; Liu Yu; Minghuan Mao (Journal of Enzyme Inhibition and Medicinal Chemistry)
Aim:A series of sulphonamide hybrids were designed, synthesised, and identified as potential lysine-specific demethylase 1 (LSD1) inhibitors.Materials and methods: Bladder cancer cell lines were cultured to evaluate the antiproliferative activity. Inhibitory evaluation of sulphonamide hybrids against LSD1 were performed.Conclusion: sulphonamide derivative L8 exhibited the antiproliferative activity against HTB5, HTB3, HT1376, and HTB1 cells with IC50 values of 1.87, 0.18, 0.09, and 0.93 μM, respectively. Compound L8 as a selective and reversible LSD1 inhibitor could inhibit LSD1 with the IC50 value of 60 nM. It effectively inhibited LSD1 by increasing the expression levels of H3K4me1, H3K4me2, and H3K9me2 in HT1376 cells. To the best of our knowledge, this was the first report which showed that sulphonamide–quinoline–dithiocarbamate hybrids potently inhibited LSD1 in bladder cancer cells. Our studies give the potential application of the sulphonamide-based scaffold for developing LSD1 inhibitors to treat bladder cancer.